Structural studies on the substitution of Ag, Na doped LCSMO CMR manganites - Subhashini, P.; Munirathinam, B.; Krishnaiah, M.; Venkatesh, R.; Venkateswarlu, D.; Ganesan, V. (AIP conference proceedings, 2016)
Synthesis and characterization of colossal magnetoresistance (CMR) materials has been a subject of scientific research due to the unique transport, magnetotransport, and magnetic properties. The single phase polycrystalline La0.7Ca0.1Sr0.1M0.1MnO3 (LCSMO) (M=Ag and Na) samples prepared using nitrate route method. The structural properties are studied at different dopants by X-ray diffraction. The surface morphology and elemental analysis of both samples were carried out by scanning electron microscopy (SEM) and energy dispersive X-ray technique (EDAX) respectively. The structural analysis shows that the LCSMO is crystallized in an orthorhombic perovskite structure belonging to Pnma space group. The crystal size of the sample is calculated using Scherrer formula. The SEM images show that the polycrystalline grains are observed to be near spherical shape and uniform in size. EDAX spectra taken from the surface of the synthesized powders show a nominal composition near the desired one for M=Na sample where as some vacancies are present in the A-site in the case of Ag substitution as will be discussed in this paper.